Magnetically Guided Viral Transduction of Gene-Based Sensitization for Localized Photodynamic Therapy To Overcome Multidrug Resistance in Breast Cancer Cells - Liao, Zi-Xian; Kempson, Ivan M; Fa, Yu-Chen; Liu, Meng-Chia; Hsieh, Li-Chen; Huang, Kuo-Yen; Wang, Li-Feng (Bioconjugate chemistry, 2017)
Chemotherapy represents a conventional treatment for many cancers at different stages and is either solely prescribed or concomitant to surgery, radiotherapy, or both. However, treatment is tempered in instances of acquired drug resistance in response to either chemotherapy or targeted therapy, leading to therapeutic failure. To overcome this challenge, many studies focus on how cancer cells manipulate their genomes and metabolism to prevent drug influx and facilitate the efflux of accumulated chemotherapy drugs. Herein, we demonstrate magnetic adeno-associated virus serotype 2 (ironized AAV2) has an ability to be magnetically guided and transduce the photosensitive KillerRed protein to enable photodynamic therapy irrespective of drug resistance.